Dependencies between model indicators of the basic and the specialized speed in hockey players aged 13-14 - Antonov, A. (Trakia Journal of Sciences, 2020)
PURPOSE The aim of our research is to establish the degrees and directions of dependence between the main forms of manifestation of the basic and specialized speed. The subject was 20 boys born in 2005 and 2006. METHODS Through tests and variance analysis (VA) we determine the level of the main forms of the basic and specialized speed, and through correlation analysis (CA) and intercriteria analysis (ICrA) we establish the existence of possible connections and degrees of dependence between them. RESULTS: By using VA we were able to characterize the average level, the level of dispersion and the distribution of the values of the studied indicators. Correlations and dependencies have been established by using CA, traditionally applied by sports science. We have also applied the innovative ICrA in order to confirm or reject the established correlations, directions and degrees of dependence. CONCLUSIONS: The conducted CA and ICrA have shown that the means for the development of the basic linear speed (BLS) and specialized linear speed (SLS) do not have a significant impact on the development of the special complex speed. ICrA also indicates a lack of correlations and dependencies between BLS and SLS, which, however, is not confirmed by CA.